Endoscopic ultrasound as an early diagnostic tool for primary sclerosing cholangitis: a prospective pilot study - Lutz, H. H.; Wasmuth, H. E.; Streetz, K.; Tacke, F.; Koch, A.; Luedde, T.; Trautwein, C.; Tischendorf, J. J. W. (Endoscopy, 2012)
Background and study aims: Primary sclerosing cholangitis (PSC) is a rare, chronic cholestatic liver disease, which typically affects middle-aged men and is frequently associated with inflammatory bowel disease. Early recognition and accurate diagnosis remains a clinical challenge. Invasive diagnostic procedures, such as endoscopic retrograde cholangiography or liver biopsy are needed when magnetic resonance cholangiopancreatography remains inconclusive. As these procedures are associated with significant risks, the current study sought to determine whether endoscopic ultrasound (EUS) of the biliary tract is a useful diagnostic tool in cases of suspected PSC.Patients and methods: In a prospective pilot study, 138 patients presenting with chronic cholestatic hepatopathy were screened and 32 patients with possible PSC were evaluated further. In addition to all routine measures, EUS was included in the diagnostic work-up. The following parameters were evaluated and compared with the definitive diagnosis: wall thickening ( ≥ 1.5 mm), irregular wall structure, significant changes of caliber of the common bile duct, and perihilar lymphadenopathy.Results: In the 138 patients screened, a PSC prevalence of 13 % was found. Of the 32 patients included in the study, 17 had large-duct PSC diagnosed. When two of the aforementioned four parameters showed PSC-like features, sensitivity and specificity of predicting PSC were 76.4 % and 100 %, with positive and negative predictive values of 100 % and 79 %, respectively. In four patients presenting with strictly intrahepatic disease, EUS was not diagnostic.Conclusions: EUS proved to be a valuable tool in suspected PSC and accurately predicted extrahepatic disease. EUS should be evaluated further as an early procedure in routine diagnostic measurements. This approach promises a significant improvement in disease detection as well as a reduction in high risk invasive procedures.